Efeito do resveratrol sobre o estresse oxidativo e lesão muscular em ratos submetidos a esforço físico intenso - Vendrame, Kelly Elisângela [UNESP] (2012)
The intense physical exercise increases the oxygen consumption and leads to oxidative stress that is able to damage muscle fibers, proteins and lipids from organism. Resveratrol (RV) is a potent antioxidant naturally found in some plants, its action is on oxidative stress caused by renal failure and diabetes, preventing and/or reducing the consequences of myocardial infarction, hypercholesterolemia, cancer and Alzheimer's disease. This study aimed to test the hypothesis that sedentary rats subjected to an intense physical and treated with RV (10mg/kg/day) for 10 days showed lower oxidative stress and muscle injury.The use of RV did not affect the metabolic profile in rats kept in rest, in the group not supplemented with RV the exercise increased plasmatic concentration of glucose (p=0,0361) and activity of aspartate aminotransferase (p=0,0476), while decreased concentration of total bilirubin (p=0,0176). An increased total antioxidant status was observed in the group supplemented with resveratrol and submitted to swimming (p<0,001). The results demonstrated that the intense physical effort in sedentary animals induced oxidative stress that can cause muscle muscle damage and that such effects can be attenuated with the use of resveratrol